Bifidobacterium, Spirulina, and Yeast extracts in low-energy diets for rabbits: effects on performance, hematology, lipid metabolism, hepatorenal function, immunity and hormones - Shaheen, Mohamed S.; Allam, Ahmed A.; Abdel Monem, Usama M.; Bassiony, Sabry M.; Khalil, Bakry A.; Salah, Ayman S.; Alawam, Abdullah S.; Rudayni, Hassan A.; Elolimy, Ahmed A.; Abass, Kasim Sakran (Frontiers in Veterinary Science, 2025)
IntroductionThis research assessed the influence of probiotics in low-energy diets on the performance and health status of rabbits during the growing phase. The growth parameters, carcass metrics, serum immunological state, lipid profile, and hepatic and renal functioning of rabbits have been analysed.MethodsOne hundred male New Zealand White rabbits, aged 5 weeks, were split into five groups at random. The rabbits within each group were allocated into 10 replicates, comprising 2 rabbits each. The initial group (T1) received a standard energy diet (10.85 MJ/kg), the (T2) group was provided with a low energy diet (10.25 MJ/kg), whereas the T3, T4, and T5 groups were administered a low energy diet mixed with Bifidobacterium (1 ml/kg diet), Spirulina extract (2 ml/kg diet), and yeast extract (2 ml/kg diet), respectively.Results and DiscussionThe results showed a significant increase in growth performance with the treatment of biological feed additives, and the group treated with spirulina extract increased final body weight and weight gain (5-13 wk), while the group treated with bifidobacterium improved feed intake and feed conversion ratio (5–13 wk). Carcass traits were not significantly affected by probiotic supplementation (P > 0.05). Moreover, haematological parameters showed no significant changes (P > 0.05) with probiotic supplementation, except for red blood cells (RBCs), white blood cells (WBCs), platelets (PLT), and basophils (BAS), which showed a significant variation (P < 0.05). Liver and kidney function tests showed a significant increase (P < 0.05) with probiotic treatments. Furthermore, thyroid hormones such as T3 and T4 were significantly enhanced by supplementation of probiotics (P < 0.0001). Immunoglobulins (IgA and IgG) were significantly enhanced by supplementation of probiotics when compared to low-energy diet group. Conclusively, probiotics in low-energy diet significantly enhanced rabbit growth, and serum immunity while improving lipid profiles and supporting liver and kidney functions. This supplementation strategy promoted both performance and overall health during the fattening period.